Diversity Of Gastropods At Intertidal Zone Of Pengudang Village Bintan Aistrict - Iskan Fami Jumaidi; Syafruddin Nasution; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted in April 2015. The study aim is to the determine the diversity of gastropods at intertidal zone of Desa Pengudang. Survey method was used to collect informations related to the purpose of the study. There were 3 stations chosen along the coast of Desa Pengudang and 15 sampling points each station. Sample of gastropods were transported to the laboratory for further analysis. The results show that there were 20 species of gastropods found through the research area which include 10 familisan, 5 orders. Diversity of gastropods (H’) was high and species dominance index was moderate, while equability index was relatively good. The dominance spesies of gastropods over the study location were Cerithium cingulata and Cerithium despectum.Keywords: Gastropods, Diversity, Intertidal Zone, Village Of Pengudang, BintanIsland